DETECTION OF HUMAN TELOMERASE ACTIVITY BY TELOMERASE TRAP ELISA ASSAY* - Wei, Lixin; Wu, Mengchao; Yan, Zhenlin; Shen, Feng; Xie, Tianpei; Qian, Qijun; Cui, Zhenfu; Shi, Junxia; Guo, Yajun (Chinese Journal of Cancer Research, 2013)
Objective: Telomeric repeat amplification protocol (TRAP) is now a conventional assay for detecting telomerase activity. However, this method presents problems related to tedious quantifying, radioisotopic handing and the limited number of samples to be examined. In order to alleviate these inconveniences, we have developed and evaluated a novel telomerase TRAPELISA assay detecting human teiomerase activity. Method: Telomerase TRAP-ELISA assay is a system based on the combination of PCR-ELISA with TRAP. Comparing with the conventional TRAP assay, we detected telomerase activity in 293 cell and negative controls (RNase-pretreated or heat-treated). Result: Telomerase activity in 293 cell is positive. The OD value of serial extracts from 10 , 102 , 103 and 104 ceils assayed by telomerase PCR-ELISA depended on the number of 293 cells in assay. RNase-pretreated or heattreated control was negative. Telomerase TRAP-ELISA deteclion yields results within one day and is handled without radioisotopes. Conclusion: Telomerase TRAPELISA assay is non-radioisotopic, fast and quantitative method for detecting human telomerase activity.